(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
With the expansion of artificial intelligence and advanced technologies, the world in the 21st century is rapidly changing and imposing new living dynamics. Although such changes affect all age groups, younger generations accept them faster and react more positively. The new cohorts - Generation Z and Alpha - live in a digital world that affect their lifestyle, interpersonal relations, quality of mental health, psychological well-being and everyday challenges. The presence of the so called “Frankenstein effect” in some adults provoked by the fast development of artificial intelligence and robotics, reflects a “humans versus machines” position, viewing artificial intelligence as a threat to humanity. However, the reality is that digital and human world are not in conflict, since many people are already using artificial intelligence tools on daily basis. It is implemented in certain aspects of medicine, education, business, law, agriculture, industry, space technology and in many other fields. With this in mind, the aspect of morality pops up as a very important one. A frequently asked question is: Does artificial intelligence have the capacity to make moral decisions independently? Therefore, integrating morality into AI algorithms is one of the priorities that interdisciplinary teams from engineering and computer sciences, psychology, philosophy, sociology, law, etc. are intensively working on. This paper addresses this issue by presenting findings from relevant research which discusses the challenges and possibilities for integrating the dimensions of morality and introducing human values into autonomous systems that perform complex tasks.